Evaluation of the effect of refined management of prospective prescription review rules for antimicrobial agents in an outpatient setting of a county-level hospital in China - Dong Pan; Zhewen Lu; Ye Yan (PLoS ONE, 2026)
Objective To explore the impact of implementing a refined management system for prospective prescription review and to provide evidence for improving the rational use of antibiotics in county-level hospitals. Methods Using the prospective prescription review system at Affiliated Yangming Hospital of Ningbo University, China, we performed a refined management of the review rules targeting major issues identified in outpatient antibiotic prescriptions. A comparative analysis was conducted to evaluate the rationality of prescriptions before and after the implementation of this refined management. Results Comparison of prescription data before and after the refined management showed that the rate of irrational outpatient antibiotic prescriptions decreased from 20.46% to 7.80%. Specifically, the proportion of prescriptions with inappropriate indications decreased from 2.65% to 0.67%. The rate of prescriptions with an inappropriate frequency of administration or unsuitable solvent decreased from 4.63% to 0.79%. Prescriptions with an inappropriate dosage or route decreased from 8.14% to 2.09%. Irrational prescriptions for special populations decreased from 1.36% to 1.21%, and those involving potential drug-drug interactions decreased from 3.68% to 3.03%. Conclusion The refined management of prospective antibiotic prescription review rules in the outpatient department of this county-level hospital significantly reduced the rate of irrational prescriptions. This strategy is worthy of promotion and application in other similar hospitals.